Development of AlTiN coated carbide bandsaw for machining titanium-17 alloy. (1st January 2014) - Khan, Fahd N.; Daadbin, Ali; Persson, Martin; Haider, Julfikar
Economical and efficient machining of titanium alloys has always been a challenge for the metal cutting industry owing to their poor machinability characteristics, such as high reactivity with tool materials. In recent years, aluminium titanium nitride (AlTiN) coating has attracted increasing attention over traditional TiN coating, due to its superior properties. Bandsawing of titanium alloys has not been investigated in a greater detail compared to other machining operations such as turning, milling and drilling. In the present investigation, AlTiN coating was deposited onto carbide tipped bandsaw teeth and the coating properties were assessed. A modified lathe machine was used for performing the machining tests. Forces experienced by the bandsaw teeth during the machining tests were measured and specific cutting energy was calculated. The results showed that the AlTiN coated bandsaw teeth performed better than the un-coated bandsaw teeth in terms of wear length, force and specific cutting energy.